Dietary supplementation of medicinal herbs with total mixed ration to mitigate enteric methane emission in sheep (Bangladesh Journal of Animal Science, 2021)
The purpose of this study was to determine the effects of pineapple wastes (Ananas comosus), garlic leaves (Allium sativum), moringa leaves (Moringa oleifera) and their combination on growth, plasma metabolites, meat characteristics and enteric methane emission in sheep. A total of 15 sheep (initial BW: 8.3±0.2 kg; age: ~ 1 year; non-descript indigenous to Bangladesh) were randomly assigned to one of five dietary treatments with three sheep per treatment in a completely randomized design. Dietary treatments were:  (1) CL-diet: a total mixed ration (TMR) pellet based on roadside grass and concentrates with a CP–16.72%  and ME–10.7 MJ/kg; (2) PW-diet: CL-diet + 10g DM of pineapple waste (peels, cores, tops, and leaves)/day; (3) GL-diet: CL-diet + 10g DM of garlic leaves/day; (4) ML-diet: CL-diet + 10g DM of moringa leaves /day; (5) HM-diet: CL-diet + 10g DM of herbal mixture (3g pineapples wastes + 3g garlic leaves + 4g moringa leaves)/day. Weekly live weight gain and plasma metabolites did not show any significant variation among the treatments. Compared to the CL-diet group, the herbal supplemented group had 18–34% lower abdominal fat content, and the lowest value was found in the GL-diet group. Furthermore, the methane emission (g/day/sheep) was reduced by 5–13% in herb supplemented groups compared to the CL-diet group. Additionally, the lamb fed GL-diet emitted the lowest enteric methane (21.26 vs 24.07 g/kg DMI) compared to other experimental groups. Overall, garlic and moringa leaves could be added to TMR to minimize fat accumulation and enteric methane emission from sheep.Bang. J. Anim. Sci. 2021. 50 (1):28-35